Identitas Komunikasi Keluarga Pelayaran dalam Membangun Keutuhan Keluarga dengan Fokus Pada Dinamika Gossip di Desa Pengkol, Sukoharjo - Patanem, Burhan Hariyo; Ramadhana, Maulana Rezi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Seafaring families maintain strong emotional and social bonds despite physical separation, with the head of the family often away for 7-9 months annually. While Pengkol Village benefits economically from residents working as cruise ship sailors, family cohesion faces risks. Parents serve as crucial communicators, fostering healthy relationships across distances. Overcoming challenges requires dedication, especially from parents, to uphold psychological well-being and familial harmony. This study explores communication identity in building shipping families' integrity in Pengkol Village, utilizing qualitative methods. Data collection involves interviews and observations. The researcher found gossiping prevalent, particularly among shipping families, who often adopt a "let it go" attitude, emphasizing the importance of transparent communication and trust to sustain unity and harmony.